Examination of Zinc and Copper Uptake by Plants in Long-term Field Experiment - Szegedi, László; Tury, Rita; Lehoczky, Éva (Journal of Central European Green Innovation, 2022)
The long-term field experiment of heavy metal loading was set up in the autumn of 1994 in the Tass-puszta Farm of the Károly Róbert College (Károly Róbert Campus, Hungarian University of Agricultural and Life Sciences). Zinc and copper uptake of plants was studied in the years 1996, 2001, 2002 when the Cu and Zn contents of plants and soil were mesaured as well. In the years of the study the experimental plants were maize (Zea mayes L.), winter barley (Hordeum vulgare L.), white mustard (Sinapis alba L) and alfalfa (Medicago sativa L.). The uptake of Cu and Zn by the plants was evaluated by determining the soil-plant transfer coefficients. Knowing the soil-plant transfer coefficient of the investigated heavy metals, it is also possible to determine the extent to which the “soluble” (NH4-acetate+EDTA) element content corresponds to the real plant microelement uptake. For this, we determined the values of the distribution ratio of each heavy metal as the quotient of the “soluble” and “total” (cc.HNO3+cc.H2O2) element content of the soil. Based on the values of soil-plant transfer coefficients, zinc was found to be more mobile than copper. The distribution ratio of zinc was on average 1/5 of the value of the transfer coefficient. This result shows that the soil has zinc reserves that can not be detected by the method of Lakanen-Erviö (1971). In the case of copper, the value of the distribution ratio and the soil-plant transfer coefficient did not differ significantly.
Keywords: heavy metals; maize (Zea mays L.); winter barley (Hordeum vulgare L.); white mustard (Sinapis alba L.); alfalfa (Medicago sativa L.); soil-plant transfer coefficient